Abies spectabilis−mediated silver nanoparticles inhibits cell growth and promotes apoptosis in breast cancer MCF-7 cells - Ren, Guanghui; Hao, Xiaoyan; Yan, Shuyi; Chen, Jun; Qiu, Guobin; Kok, Pian Ang; Mohd Tamrin, Mohd Islahuddin (Begell House, 2022)
Breast cancer is the second most cause of mortality among women worldwide due to the uncontrolled proliferation of tumor cells in the mammary epithelial tissues. The silver nanoparticles were formulated from the Abies spectabilis leaf (AS-AgNPs) and characterized by various practices like UV-vis spectroscopy, FTIR, SEM, and XRD. The in vitro anticancer potential of fabricated AS-AgNPs against the MCF-7 cells were analyzed. The MTT test was executed to investigate the cytotoxic nature of fabricated AS-AgNPs against MCF-7 cells. The magnitudes of ROS accumulation and MMP level in the AS-AgNPs supplemented MCF-7 cells were studied using fluorescent staining techniques. Caspase activities were studied using assay kits. The contents of oxidative stress and antioxidant biomarker (TBARS, SOD, CAT, and GSH) levels were scrutinized by standard methods. The expressions of apoptotic markers like Bax and Bcl-2 in the AS-AgNPs administered MCF-7 cells were detected by RT-PCR assay. The MTT findings showed that both extract and fabricated AS-AgNPs remarkably decreased the MCF-7 cells. Nonetheless, both plant extract and AS-AgNPs did not affect the cell viability of MCF-10A cells. Furthermore, the fabricated AS-AgNPs improved the ROS accumulation, and depleted the MMP status in the MCF-7 cells. AS-AgNPs administered MCF-7 cells demonstrated the improved TBARS content and depleted antioxidants. The treatment with AS-AgNPs considerably elevated the caspase-9 and -3 activities and Bax expression, while decreasing the Bcl-2 expression in MCF-7 cells. Hence the current investigation reports that the formulated AS-AgNPs exhibited remarkable in vitro anticancer action against MCF-7 cells through increased ROS, oxidative stress, and apoptotic protein expression. The fabricated AS-AgNPs could be a possible anticancer remedy in the future.